Precision Matters: Repeatability and Reproducibility of Total PSA and Homocysteine Measurements in Alinity i-System - Grari, Oussama (Journal of Medical Biochemistry, 2024)
Introduction: The precision of test measurements is critical in clinical diagnostics, especially for biomarkers like total PSA and homocysteine, which are essential to disease assessment. Using the CMIA approach, this study investigates the repeatability and reproducibility of these biomarkers on the Abbott Alinity system. Materials and methods: The present study was conducted in the clinical chemistry laboratory at Mohammed VI University Hospital of Oujda. The evaluation of the Alinity i-system’s analytical performance for total PSA and homocysteine focused on assessing repeatability and intermediate fidelity. The assessment followed the protocols and guidelines established by the French Society of Clinical Biology (SFBC). Results: Our analysis yielded favorable findings regarding the performance of the Alinity assays. The coefficients of variation for both the intra-assay and inter-assay precision were less than 5.89% and 4.29%, respectively. These findings underscore the tests’ precision and consistency, affirming the CMIA method’s reliability in accurately measuring total PSA and homocysteine levels. Conclusion: Our assessment of the Alinity i-system for total PSA and homocysteines showed significant analytical performance. Yet, limitations due to excluding critical parameters hindered a comprehensive evaluation. Addressing these in future investigations is crucial for upholding high diagnostic standards.